History's Peru : The Poetics of Colonial and Postcolonial Historiography - Thurner, Mark (Book collections on Project MUSE., 2011)
Thurner examines the development of Peruvian historical thought from its misty colonial origins in the 16th century up to the present day. He shows that the concept of 'Peru' is both a strange and enlightening invention of the modern colonial imagination - an invention that lives on today as a postcolonial wager on a democratic political future that can only be imagined in its own historicist terms, not those of European or Western history.